„Studia Socjologiczno-Polityczne” 1958–1968 - Wiatr, Jerzy J. (Studia Socjologiczno-Polityczne. Seria Nowa, 2014)
The history of political sociology studies is closely tied to the rebirth of Polish sociology after 1956. The chair of political sociology at the Warsaw University was created by Julian Hochfeld (1911–1966), who was a founder and an editor of the journal. The journal reflected the “open Marxism” of the Hochfeld school and was the main theoretical organ of critical political thinking in Poland. Twenty five issues of the journal were devoted to key political problems of Poland and of the foreign countries. In 1968, in the climate of antidemocratic and antisemitic campaign launched by the commiunist authorities, the journal was closed.